The effects of Bifidobacterium Bifidum (BBCWF) on proliferation of K562 cell line - Leila zarei; mysam abtahi foroshani; Atefeh Garajedagi; Hadi Esmaeili govarchin galeh (Fasa University of Medical Sciences, 2017)
Background & Objective: In the previous studies, the beneficial effects of oral administration of probiotic bacteria in treatment of some gastrointestinal cancer have been documented. The main aim of this study was to evaluate the direct effects of the bacterial cell wall extract Bifidobacterium bifidum on proliferation of human erythromyeloid cancer cell line K562. Material & methods: After culturing the bacteria, and preparing cell wall fractions, dilutions of 1000, 2000, 4000 and 8000 µg/ml bacteria cell walls were prepared in sterile conditions. K562 cells and peripheral blood mononuclear cells (PBMC) were cultured in a conventional manner in the presence of different concentrations of bacteria from cell wall extract with the doxorubicin concentration of 0.1 mM. In order to assess the anticancer property of the abovementioned extract the MTT test was utilized. The T-Student test was used in order to analyze the data using SPSS 21. Results: The minimum effective concentration of bacteria extract on the viability of K562 cells and PBMC was 2000 and 4000 µg/ml, respectively. Conclusion: The selected bacterial extract killed more cancer cells than PBMC cells.